Financial Performance Analysis of the West Java Provincial Occupational Health Hospital Before and After PPK-BLUD Implementation (2020-2024) - Ferlycia Aida Wardani; Nunung Aini Rahmah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The implementation of Regional Public Service Agency Financial Management Pattern (PPK-BLUD) represents a significant policy shift aimed at enhancing efficiency, effectiveness, and accountability in regional public hospital financial governance while improving public health service quality. This study aims to analyze and compare the financial performance of RSUD Kesehatan Kerja of West Java Province before (2020–2023) and after (2024) the implementation of PPK-BLUD, following its BLUD designation in 2023. Based on 2022 Inspectorate audit reports and financial statement analysis from 2020-2024, pre-BLUD implementation revealed financial deficits and suboptimal performance indicator achievement. Post-implementation showed increased operational revenue, financial surplus, and improved SPM achievement. This quantitative descriptive research utilized financial reports from 2020-2024, analyzing data through financial ratios based on Director General of Treasury Regulation No. Per-24/PB/2018. Statistical analysis employed Kolmogorov-Smirnov normality tests and Paired Sample T-Tests using SPSS version 30. Results demonstrated that five of eight financial ratios showed significance values < 0.05, indicating statistically significant differences before and after PPK-BLUD implementation. The hospital's financial performance score improved substantially, achieving "Good" category status in 2024. The evidence confirm that PPK-BLUD implementation positively impacted financial management effectiveness and efficiency at RSUD Kesehatan Kerja of West Java Province. This policy transformation successfully addressed previous financial challenges, demonstrating measurable improvements in operational revenue generation, deficit elimination, and overall financial performance indicators, thereby validating the strategic value of BLUD adoption in regional public hospital financial management systems.